A avaliação como dispositivo pedagógico: capturas discursivas significadas no contexto da educação de surdos - Camillo, Camila Righi Medeiros (2008)
The present dissertation, Evaluation as a pedagogical device: discursive captures signified in the context of deaf education , aims at focusing on evaluation issues in the field of deaf education. In this sense, there has been an attempt to problematize some discursive regularities in narratives produced by deaf teachers that are daily involved in pedagogical practices in deaf schools, i.e. discourses that work as strategies to both discipline and regulate the conduct of deaf students and teachers. From an analysis of relationships between power, knowledge and truth, this work has attempted to understand the strategic productivity organized and established in a current discourse - that of evaluation in the deaf education context - which leads us to see and say particular forms, taken as natural and true, of an object that does not transcend history, rather, that both establishes itself and is fabricated in it. In order to do so, a set of tools extracted from the field of Cultural Studies in Education have been used, mainly those that are closer to a post-structuralist perspective; among them, are Foucauldian notions of power, normalization and discourse. This work has also approached evaluation in the school as a historical, cultural invention that, in turn, also invents others, denominated deaf subjects. Evaluation has been problematized through the perspective of discipline, and discussed as a practice that operates by means of power mechanisms and disciplinary strategies to produce the student subject. This research has thought about evaluation from the experiences of deaf difference, drawing attention to the problematization of the so-called Pedagogy of Difference, as Pedagogy is a knowledge/power field that paralyzes, captures, names difference. As it is impossible to think about evaluation within a perspective that is incompatible with differences, it has been here signified through what might be called experiences of difference , also considering knowledge/power relations that impregnate those practices in the art of evaluating .